2010
DOI: 10.1037/a0018235
|View full text |Cite
|
Sign up to set email alerts
|

Exposure therapy for posttraumatic stress disorder in a residential substance use treatment facility.

Abstract: Clinical lore abounds when discussing the issue of treating trauma-related symptoms in substance dependent clients. Historically, clinicians have wondered whether they should wait until the client has gained substantial abstinence from abused substances before initiating trauma treatment or if trauma treatment should be conducted during substance use treatment. Furthermore, questions arise with regard to exactly how trauma-related symptoms should be addressed and how trauma treatment should be incorporated int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 37 publications
1
26
0
Order By: Relevance
“…Foa and Yusko reported similar outcomes for a study with PTSD and alcohol dependence comorbidity [31]. In a review of the literature on treatment of comorbid substance abuse and PTSD, Henslee and Coffey provide empirically based specific suggestions for the use of PE as part of a residential substance abuse and PTSD program [34]. Thus, people with PTSD and comorbid conditions appear to benefit from PE, both for PTSD symptoms and comorbid conditions.…”
Section: Resultsmentioning
confidence: 73%
See 1 more Smart Citation
“…Foa and Yusko reported similar outcomes for a study with PTSD and alcohol dependence comorbidity [31]. In a review of the literature on treatment of comorbid substance abuse and PTSD, Henslee and Coffey provide empirically based specific suggestions for the use of PE as part of a residential substance abuse and PTSD program [34]. Thus, people with PTSD and comorbid conditions appear to benefit from PE, both for PTSD symptoms and comorbid conditions.…”
Section: Resultsmentioning
confidence: 73%
“…These trials, as well as additional research in clinic settings, include populations that have previously been ruled out of PE studies (i.e., active suicidal risk [50][51], substance dependence [31,34], psychotic disorder [52][53]). Such studies will continue to close the gap as we learn how to apply PE to patients with these severe comorbidities who experience PTSD.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, in view of high PTSD rates in SUD inpatients and high dropout rates during detoxification treatment [11], not addressing trauma/PTSD in early detoxification treatment bears a substantial risk of leaving patients without adequate diagnosis and treatment and putting them at an increased risk for dropout and a less favorable treatment outcome [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Drug abuse services have traditionally advocated a sequential treatment of substance abuse and other psychiatric disorders like PTSD in order to protect their clients during the stressful and emotionally overwhelming period of withdrawal symptoms. However, recently this basic assumption has been questioned [42] . It has been demonstrated that including trauma treatment in substance use treatment is safe and does not produce more adverse events [43] , and that it has positive effects on the course of the substance use disorder [44] .…”
Section: Discussionmentioning
confidence: 99%